(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Kautilya’sArthashastra describes not only the internal Administration but the externalbehavior of the state also. All the basic principles of inter - state relationsare given in Arthashastra. He agrees with imperialism and describes the way towin a state. Kautilya deals with foreign policy, so he is popularly known asthe great theorist of interstate relations because of his unique andunprecedented contributation.1